β-arrestin-1 and β-arrestin-2 Restrain MRGPRX2-Triggered Degranulation and ERK1/2 Activation in Human Skin Mast Cells - Wang, Zhao; Li, Zhuoran; Bal, Gürkan; Franke, Kristin; Zuberbier, Torsten; Babina, Magda (Frontiers in Allergy, 2022)
As a novel receptor that efficiently elicits degranulation upon binding to one of its numerous ligands, MRGPRX2 has moved to the center of attention in mast cell (MC) research. Indeed, MRGPRX2 is believed to be a major component of pseudo-allergic reactions to drugs and of neuropeptide-elicited MC activation in skin diseases alike. MRGPRX2 signals via G proteins which organize downstream events ultimately leading to granule discharge. Skin MCs require both PI3K and ERK1/2 cascades for efficient exocytosis. β-arrestins act as opponents of G proteins and lead to signal termination with or without subsequent internalization. We recently demonstrated that ligand-induced internalization of MRGPRX2 requires the action of β-arrestin-1, but not of β-arrestin-2. Here, by using RNA interference, we find that both isoforms counter skin MC degranulation elicited by three MRGPRX2 agonists but not by FceRI-aggregation. Analyzing whether this occurs through MRGPRX2 stabilization under β-arrestin attenuation, we find that reduction of β-arrestin-1 indeed leads to increased MRGPRX2 abundance, while this is not observed for β-arrestin-2. This led us speculate that β-arrestin-2 is involved in signal termination without cellular uptake of MRGPRX2. This was indeed found to be the case, whereby interference with β-arrestin-2 has an even stronger positive effect on ERK1/2 phosphorylation compared to β-arrestin-1 perturbation. Neither β-arrestin-1 nor β-arrestin-2 had an impact on AKT phosphorylation nor affected signaling via the canonical FceRI-dependent route. We conclude that in skin MCs, β-arrestin-2 is chiefly involved in signal termination, whereas β-arrestin-1 exerts its effects by controlling MRGPRX2 abundance.